On Cyclicality in the Current and Financial Accounts : Evidence from Nine Industrial Countries - Clausen, Jens.; Kandil, Magda (Washington, D.C. : International Monetary Fund, 2005)
The paper investigates cyclical fluctuations in the current and financial (formerly capital) accounts of the balance of payments and major underlying components for nine industrial countries. The empirical model uses as explanatory variables domestic output growth, price inflation, real exchange rate fluctuations, energy price inflation, global growth, and regional growth. The evidence from the estimation of the model indicates the importance of fluctuations in output growth to the cyclicality of the current and financial account balances. The necessary and sufficient condition to sustain a large current account deficit is high domestic growth, which tends to stimulate financial inflows and provides adequate resources for financing. Other factors appear to be less important to the cyclicality of the current and financial account balances and their negative correlations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet